Relationship Marketing: An overview - Dasari, Shailendra; Gunaseelan, Rupa (Indian Journal of Marketing, 2012)
Relationship marketing prevalent in the pre-industrial era had to give way to transactional marketing in the post-industrial era. However, it has been staging a strong comeback for the past two decades, thereby making the circle complete. This article is an attempt to trace the re-emergence of relationship marketing - it presents the pros and cons of several theories and models elucidating this phenomenon and updates the readers with the literature that has surfaced in the last 20-25 years across the continents on the subject based on the research conducted during April - August 2011. The future of Relationship Marketing (RM) and the existing disconnect between CRM (Customer Relationship Management) and RM has also been discussed in the present paper . As a chronicle that provides an overview of RM spanning a few centuries, this paper, it is hoped, would be a useful reference document for both researchers and practitioners of marketing.